Compactibility of cohesive soils from tablelands as influenced by cassava wastewater - Gonçalves, Raissa Homem; Nóbrega, Júlio César Azevedo; Santos, Davi Ney; da Silva, Reginaldo Barboza [UNESP]; Ajayi, Ayodele Ebenezer; de Lima, José Maria (FapUNIFESP (SciELO), 2023)
Consolidation tests give important insights into soil compactibility. However, it requires equipment that is not always available. The costal tablelands in Northeastern Brazil have extensive areas of cohesive soils where compaction is an expressive problem. This region is a prominent producer of food and fibers with cassava as one of the leading products. Part of the cassava is used for flour production, generating wastewater, which is often applied as organic fertilizer to the soil. This can affect the compaction properties of soil due to its dispersing-flocculating characteristics. Uniaxial-compression tests and mathematical models are the primary methods to measure or estimate soil compaction. This study measured soil compression with a centrifuge, seeking a simple-quick method. We used specific loads (stainless-steel cylinders: mass) and increasing G-force (weight) to simulate the pressure on the samples used in most consolidation apparatus. Soils, sampling layers, and the presence of cassava wastewater (manipueira) were also compared since they may affect compactibility-related attributes. Samples of a Gray Cohesive Argisol and Dystrocohesive Yellow Latosol (depths of 0-0.20 m and 0.20-0.40 m) from the Tablelands of the state of Bahia, Brazil, were used. Wastewater affected water-dispersible clay, aggregate stability, pH, ∆pH, flocculation, and organic carbon, thus influencing compactibility but not the moisture and maximum density measured by the Proctor test. Centrifugation caused lower density than the Proctor test. The results were close to those estimated by the mathematical models, thus considered a promising alternative to estimating consolidation. This method also provides insight into the root growth-limiting density and the moisture content that leads to it.
Compactabilidade de solos coesos dos tabuleiros costeiros do nordeste sob influência de água residuária de mandioca
Keywords: centrifugation; G-force; moisture content; Preconsolidation pressure; soil density